Persistent threats need persistent counteraction: Responding to PCB pollution in marine mammals. (October 2017) - Stuart-Smith, Sarah J.; Jepson, Paul D.
Abstract: Polychlorinated biphenyls (PCBs) are a type of persistent organic pollutant (POP) that continues to pose a significant environmental threat to humans and wildlife. Recent scientific evidence shows that very high PCB concentrations are still major causes of contemporary declines in European cetacean populations, and potentially other marine apex predators globally. Currently, controls on PCBs are insufficient, on their own, to fully protect human health or to conserve wildlife. Although the Stockholm Convention provides a global framework to address PCBs, there appears to be a systemic shortfall of many parties of the Convention to provide sufficient prioritisation and resources for effective implementation. A 2015 United Nations Environment Programme assessment estimates that the vast majority of PCB-contaminated equipment and materials, around 14 million tonnes, still requires elimination. At present rates of PCB elimination or mitigation, many countries, including some European countries, will not achieve the 2025 and 2028 targets of the Stockholm Convention. It is imperative that the Conference of the Parties for the Stockholm Convention conclude article 17 negotiations on a compliance mechanism for the Convention as soon as possible. To help mobilise global efforts towards eliminating the threat from PCBs, an enforceable, effective and robust compliance mechanism should be established, along with capacity building support for developing countries. In Europe, renewed action is needed to reduce PCB contamination, in order to prevent some killer whale ( Orcinus orca ) and other dolphin populations from continuing to slowly decline, potentially towards extinction.